2018
DOI: 10.3389/fpls.2018.00299
|View full text |Cite
|
Sign up to set email alerts
|

Can Leaf Water Content Be Estimated Using Multispectral Terrestrial Laser Scanning? A Case Study With Norway Spruce Seedlings

Abstract: Changing climate is increasing the amount and intensity of forest stress agents, such as drought, pest insects, and pathogens. Leaf water content, measured here in terms of equivalent water thickness (EWT), is an early indicator of tree stress that provides timely information about the health status of forests. Multispectral terrestrial laser scanning (MS-TLS) measures target geometry and reflectance simultaneously, providing spatially explicit reflectance information at several wavelengths. EWT and leaf inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
0
23
1
Order By: Relevance
“…At the wavelength used here, vegetation surface reflectivity (and thus point amplitude) relates to leaf water content (Junttila et al. ) and soil moisture (Zlinszky et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the wavelength used here, vegetation surface reflectivity (and thus point amplitude) relates to leaf water content (Junttila et al. ) and soil moisture (Zlinszky et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…It is low for tall canopies where the light energy is distributed between a number of returns, for complex or opaque surfaces such as leaves, and for surfaces with low reflectivity. At the wavelength used here, vegetation surface reflectivity (and thus point amplitude) relates to leaf water content (Junttila et al 2018) and soil moisture (Zlinszky et al 2014).…”
Section: Lidar Datamentioning
confidence: 99%
“…However, no successful attempts to utilize such systems to estimate EWT at the canopy level in field campaigns have been reported in the literature, as these systems are still considered proof-of-concept. Junttila, et al [44] and Elsherif, et al [38] showed that intensity data from commercially-available NIR and SWIR TLS systems can be combined to calculate the NDI, reporting a high correlation between the NDI and EWT at the leaf level for coniferous and broadleaf species, respectively. At the canopy level, Junttila, et al [45] used an NDI of 905 and 1550 nm wavelengths with the FARO S120 and FARO X330 TLS instruments, respectively, to detect European spruce bark beetle infestation symptoms in 29 mature Norway spruce trees.…”
Section: Index Formulamentioning
confidence: 99%
“…A clear linkage between leaf water content, measured as equivalent water thickness (EWT), and TLS intensity has been shown in several studies (Elsherif et al, 2019a;Gaulton et al, 2013;Junttila et al, 2018Junttila et al, , 2016. Reflectance at the 1550 nm wavelength, which is often utilized in TLS sensors, increases as the leaf water content decreases (Junttila et al, 2016;Rallo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%